Integration of Multi-Region Material Balance Equation with Binomial Productivity Equation for Performance Prediction - Yan Liu; Langtao Zhu (Geofluids)
In order to overcome the limitations of conventional material balance methods, a new multi-region material balance method, considering the strong heterogeneity and low-velocity non-Darcy flow characteristics of bio-reef gas reservoir, is proposed to estimate the development performance of reef reservoirs. Firstly, the reef reservoir is divided into two regions, the reef cover high-permeability development area and the reef edge low-permeability supplying area. Then, based on one-dimensional non-linear seepage mechanism and mass conservation principle, the multi-region supplying material balance equation is established. Finally, combined with the binomial productivity equation, the development performance can be easily estimated at different P/Z curves. The application results indicate that the low-permeability replenishment area plays an important role, especially after entering the decline stage, on the development performance of high-permeability region. Compared with the traditional material balance method, the new method can help for better understanding of unbalanced development in different regions and the replenishment effect of low-permeability region.